Religion Moderation in Heterogenity Perspective in Jungjang Village Arjawinangun - Komara, Siti (Devotion : Journal of Research and Community Service, 2020)
One of the features of Jungjang Village is the heterogeneity of religion, there are even houses of worship of several religions in one area. The heterogeneity of religion itself is a variety of systems for ways of worshiping God Almighty and interactions with adherents of other faiths. Since a long time ago, tolerance has been deeply embedded there. However, it is feared that lately the rise of religious issues will erode existing tolerance. In order to address the existing diversity in order not to create divisions, religious moderation is needed. Moderation or moderation, namely not being extreme or not exaggerating towards a view, but must find a middle way. The method used by researchers is a qualitative type with unstructured observation and structured interviews as data collection techniques. After conducting research for two weeks, it was found that the moderation attitude in Jungjang Village was still strong so that tolerance was still closely intertwined amid the heterogeneity that existed there